MEASURING THE QUALITY OF FINANCIAL REPORTING BY USING THE ACCRUALS QUALITY MODEL AND ITS ROLE IN RATIONALIZING ADMINISTRATIVE DECISIONS (AN APPLIED STUDY IN A SAMPLE OF BANKS LISTED IN THE IRAQ STOCK EXCHANGE) - Hayder Oudah Kadhim; Mustafa Hazem Maan (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
The research aims to address the theoretical framework for the quality of financial reporting, and to focus on the models that can be used to measure the quality of financial reporting, especially the quality of receivables model. The research also aims to show the role of this in rationalizing administrative decisions. The research was applied in a sample of banks listed in the Iraq Stock Exchange. The financial period (2017-2020). The receivables model was also used to measure the quality of financial reporting in the research sample banks. The research reached a set of conclusions, the most important of which were: There is a possibility to measure the quality of financial reporting using the receivables model in the research sample, The research also concluded that the information resulting from measuring the quality of financial reporting is subject to review and verification of reliability, and the management of the research sample banks understands the results reached as a result of measuring the quality of financial reporting, as well as the availability of sufficient time in these banks to measure the quality of reporting. There is a possibility of communicating the results of measuring the quality of financial reporting to the management in order to assist in making decisions at the appropriate times.